Competence of Science Foundation students in some simple strategies for problem solving - Mailoo Selvaratnam; Nkosana Mavuso (South African Journal of Science)
The competence of over 300 Science Foundation students in five important problem-solving strategies was studied at the North-West University over a period of three years. The study method adopted was the analysis of students' answers to carefully designed questions that tested whether they competently used the following strategies for problem solving: clarifying problems by presenting them clearly, identifying explicitly the principles and laws associated with the solutions, focusing sharply on the goal, using equations for deductions and calculations and proceeding step-by-step with the solution. The results showed that their competence in the use of intellectual strategies was very poor. This lack of competence could be expected to lead to lack of self-confidence and could also seriously handicap their learning throughout their courses. We suggest that greater emphasis should be placed, in all science courses, on the training of students in intellectual skills and strategies. Such training should be integrated with the teaching of subject content throughout the courses.